Implementing Project-Based Language Learning and Teaching in Classrooms: EFL Teachers’ Perspectives - Mouni, Ram Bahadur (KMC Journal, 2022)
This study explores secondary level English as a foreign language (EFL) teachers’ perceptions about Project-Based Language Teaching (PBLT) in terms of its benefits in EFL classrooms. Moreover, it investigates the challenges EFL teachers face while implementing it in English language instruction and recommends the solutions as perceived by the EFL teachers in the EFL context of Nepal. Backing up with theoretical perspectives on PBLT approach, this study adopts phenomenological qualitative research design to analyze the data obtained from the in-depth interviews conducted with three secondary level EFL teachers from three schools of Kailali district of Nepal. This study reveals that even though EFL teachers have knowledge about the importance and benefits of using PBLT in English language teaching, they still face some ideological, pedagogical and operational challenges in effective implementation of PBLT in classrooms. However, the EFL teachers suggest some solutions to overcome the challenges for successful implementation of PBLT for better language teaching and learning.